Bcl‐2 Inhibition to Overcome Memory Cell Barriers in Transplantation. Issue 2 (February 2014) - Cippà, P. E.; Gabriel, S. S.; Kraus, A. K.; Chen, J.; Wekerle, T.; Guimezanes, A.; Wüthrich, R. P.; Fehr, T.
<x xml:space="preserve">Abstract</x> Memory T cells (Tm) represent a major barrier for immunosuppression and tolerance induction after solid organ transplantation. Taking into consideration the critical role of the intrinsic apoptosis pathway in the generation and maintenance of Tm, we developed a new concept to deplete alloreactive Tm by targeting Bcl‐2 proteins. The small‐molecule Bcl‐2/Bcl‐XL inhibitor ABT‐737 efficiently induced apoptosis in alloreactive Tm in vitro and in vivo and prolonged skin graft survival in sensitized recipients. A short course of ABT‐737 induction therapy prevented Tm‐mediated resistance in a donor‐specific transfusion model and allowed mixed chimerism induction across Tm barriers. Since Bcl‐2 inhibitors yielded encouraging safety results in cancer trials, this novel approach might represent a substantial advance to prevent allograft rejection and induce tolerance in sensitized recipients.